Mandat Ilahi dalam Hukum Kasih Menurut Matius 22:39 - Samuel Elkana (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
AbstractGod's command to obtain eternal life is by doing the law of love. The mandate to love God andneighbor was given to mankind. Sometimes humans fail to carry out the divine mandate regardingthe law of love because of a lack of understanding of the law of love. This research explainscomprehensively and theologically by using qualitative methods, namely literature studies